Determination of Human Development Index (HDI) in Malaysia (Year 1996-2022) - Mohammad Ahfadz Irsadilah; Eni Setyowati (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims to examine the effects of selected macroeconomic and social indicators on the Human Development Index (HDI) in Malaysia from 1996 to 2022.Methodology: This research applies a quantitative approach using annual time series data. The variables include economic growth (GDP), urbanization rate (UP), unemployment rate (UNEMP), real interest rate (RIR), and government health expenditure (HEALTHEXP). The data are analyzed using multivariate regression with the Ordinary Least Squares (OLS) method.Results: The findings indicate that all variables simultaneously have a significant influence on Human Development Index, with an Adjusted R2 of 0,947. Urbanization and unemployment rates negatively and significantly effect human development. Economic Growth and real interest rates show positive but statistically insignificant effects. Government spending on health is found to have a significant negative impact on Human Development Index.Applications/Originality/Value: This study provides updated empirical evidence on the macroeconomic determinants of human development in Malaysia. The result offer policy relevant insights for controlling urbanization, reducing unemployment, and improving the effectiveness of health spending to enhance human development outcomes.